Effect of Gelam honey on the oxidative stress-induced signaling pathways in pancreatic hamster cells - Ismail, I.S.; Batumalaie, K.; Safi, S.Z.; Mohd Yusof, K.; Sekaran, S.D.; Qvist, R. (Hindawi Publishing Corporation, 2013)
Oxidative stress induced by reactive oxygen and nitrogen species is critically involved in the impairment of